2017
DOI: 10.5625/lar.2017.33.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic responses to an anticancer drug in three stocks of ICR mice derived from three different sources

Abstract: Korl:ICR mice, established by the Korean National Institute of Food and Drug Safety Evaluation (NIFDS), are characterized based on their genetic variation, response to gastric injury, and response to constipation inducers. To compare the inhibitory responses of ICR stocks obtained from three different sources to the anticancer drug cisplatin (Cis), alterations in tumor volume, histopathological structure, and toxicity were examined in Sarcoma 180 tumor-bearing Korl:ICR, A:ICR (USA source), and B:ICR (Japan sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…To further validate our aforementioned results, we investigated the difference in the magnitude of response to acute exercise. Consistent with our recent observations and those of other studies involving the same ICR lineages [ 3 , 5 7 ], the results revealed a higher level of LDH in B:ICR mice than in Korl:ICR mice, accompanied with a sharp decline in the blood glucose level coupled with an increase in exercise intensity. However, we did not observe significant mouse lineage-dependent differences with respect to biological properties (e.g., body weight and muscle tissue mass) and the level of corticosterone and MDA, although they showed a tendency to increase linearly with increase in exercise intensity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To further validate our aforementioned results, we investigated the difference in the magnitude of response to acute exercise. Consistent with our recent observations and those of other studies involving the same ICR lineages [ 3 , 5 7 ], the results revealed a higher level of LDH in B:ICR mice than in Korl:ICR mice, accompanied with a sharp decline in the blood glucose level coupled with an increase in exercise intensity. However, we did not observe significant mouse lineage-dependent differences with respect to biological properties (e.g., body weight and muscle tissue mass) and the level of corticosterone and MDA, although they showed a tendency to increase linearly with increase in exercise intensity.…”
Section: Discussionsupporting
confidence: 93%
“…Among the diverse lineages of rodents supplied by major vendors of laboratory animals, the ICR mouse, developed in 1945 at the Institute of Cancer Research (ICR), is commonly used in the research field of genetics, neurobiology, immunology, and pharmacology (drug efficacy and safety). This has led to the development of several lineages of ICR mouse worldwide for various research purposes [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICR mice are one of the most popular strains of outbred mice used in in pharmacology and oncology studies. This strain have been used extensively in toxicology and pharmacology studies and is often used for product safety testing (21)(22)(23)(24)(25)(26). Animal care and all experiments were in accordance with institutional guidelines and were approved by the Institutional Animal Care and Use Committee, Sackler Faculty of Medicine, Tel-Aviv University, ID TAU-R 100106.…”
Section: Experimental Design In Micementioning
confidence: 99%